THE EFFECT OF NUTRITION EDUCATION AND GYMNASTICS CREATIONS OF SASAK (Rudat dance) AGAINST WEIGHT CHANGE, BMI, AND LIPID PROFILE TO OVERWEIGHT STUDENTS AT NUTRITION DEPARTMENT OF POLITEKNIK KESEHATAN MATARAM - Retno Wahyuningsih; Ni Putu Anita Candri; Siti Noor Aulya Faridha (poltekkes kemenkes mataram, 2018)
Abstract: The lifestyle changes in some societies today lead to a modern lifestyle, including dietary changes that change to the selection of foods with high energy and fat. Excessive energy consumption becomes the cause of obesity. Obesity, in addition becomes a health problem, also a problem for one's appearance. Obesity is associated with lipid profile. Obesity interventions can be done by setting the diet through nutrition education and exercise in the form of gymnastics creations dance exercises. Objective study was to know the effect of nutrition education (REST diet) and gymnastics creations (Rudat dance) against weight change, BMI, and lipid profile to overweight students at Nutrition Department of Politeknik Kesehatan Mataram. Research Method was Quasi experiment, randomized pre-post control group to 33 students, age 18-22 years. The data were analyzed by Univariat for the distribution of research variables and Bivariate test with different test of Paired t-test. There was significant weight loss in group 1 (χ ± SD: 0.35 kg ± 0.43, p: 0.030), and group 3 (1.72 ± 1.78, p: 0.014). While on IMT decrease in. group 1 (0.15 kg/m2 ± 0.19, p: 0.033), and group 3 (0.68 ± 0.63, p: 0.008). As for the lipid profile, there was no decrease in blood cholesterol levels, and there was a decrease in triglycerides in group 3 (24.4 ± 28.59, p: 0.024). Keywords: Education REST Diet, Creative Gymnastics, Weight, BMI, Lipid Profile, Excess Weight.